Interpreting the deformation phenomena of a levee damaged during the 2012 Emilia earthquake. Issue 124 (September 2019) - Chiaradonna, Anna; Tropeano, Giuseppe; d'Onofrio, Anna; Silvestri, Francesco
Abstract: The May 20th, 2012 Emilia earthquake triggered significant fractures, deformations and liquefaction occurrences along a number of riverbanks located close to the epicentre area. One of the most severely damaged earth structures was a levee of an irrigation channel, where large, longitudinally-oriented ground cracks were observed along a 3 km stretch. The ground fissuring was apparently associated to a lateral spreading mechanism causing structural damage to the buildings settled on the bank crown. An extensive study, including in-situ and laboratory investigations permitted a detailed definition of the geotechnical model and to back-figure the reference input motion at the deep bedrock. On such a basis, a dynamic effective stress analysis was carried out on a representative cross-section of the dyke showing that liquefaction occurred within the soil constituting the foundation of the levee. The results of the analysis allowed also for computing the permanent displacement along the critical sliding surface, which turned out to be compatible with the observed damage. Highlights: An accurate site characterization was possible based on high-quality field and lab tests. The reference ground motion was back-figured by deconvolution of a seismic record. A simplified model allowed predicting excess pore pressure by a 1D numerical code. Sliding displacements computed by a hybrid procedure were similar to those observed.